2012
DOI: 10.1155/2012/945205
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Benefit of Allopurinol in the Treatment of Foreign Body Granulomas Caused by Polymethylmethacrylate Microspheres

Abstract: Injectable polymethylmethacrylate (PMMA) microspheres are nonbiodegradable and too large for macrophage phagocytosis. There are several complications possible to happen, like chronic nonspecific inflammatory reactions, lip stiffness, infection, and granulomas. The occurrence of granulomas can lead to a not aesthetic result, making some extreme changes in the patient's life. The objective of this case report is to describe the successful treatment of foreign body granulomas caused by polymethylmethacrylate micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It has also been reported that silicone granulomas have successfully been treated with minocycline only [ 46 , 47 , 48 ]. In addition, the systemic treatment of foreign body granulomas using allopurinol [ 49 , 50 ], colchicines [ 51 ], and cyclosporine [ 52 ] has been reported.…”
Section: Treatmentmentioning
confidence: 99%
“…It has also been reported that silicone granulomas have successfully been treated with minocycline only [ 46 , 47 , 48 ]. In addition, the systemic treatment of foreign body granulomas using allopurinol [ 49 , 50 ], colchicines [ 51 ], and cyclosporine [ 52 ] has been reported.…”
Section: Treatmentmentioning
confidence: 99%
“…11 More widely available, PMMA is a synthetic polymer that can be used to prepare 30-40 μm microspheres with a regular or porous surface; in addition, PMMA can be used for other applications in the health tissue area, such as in contact lenses and esophageal implants. 12 In clinical orthopedic settings, PMMA in spacer or bead forms acts as a drugdelivery vehicle and releases high concentrations of antibiotics to the surrounding tissues; PMMA has been regarded as the gold standard in the prophylaxis and treatment of bone infections. 13,14 Nevertheless, the use of PMMA remains debatable due to its lack of osteointegration properties and the need for extra surgical procedures for removal and reconstruction surgery, leading to a risk of contamination at the surgical site.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, thermostable antibiotics have been commonly incorporated into polymethylmethacrylate (PMMA) cement 11 . More widely available, PMMA is a synthetic polymer that can be used to prepare 30–40 μm microspheres with a regular or porous surface; in addition, PMMA can be used for other applications in the health tissue area, such as in contact lenses and esophageal implants 12 . In clinical orthopedic settings, PMMA in spacer or bead forms acts as a drug‐delivery vehicle and releases high concentrations of antibiotics to the surrounding tissues; PMMA has been regarded as the gold standard in the prophylaxis and treatment of bone infections 13,14 .…”
Section: Introductionmentioning
confidence: 99%